Dynamic Business Process Formation for Instant Virtual Enterprises - Mehandjiev, Nikolay; Grefen, Paul.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2010)
Dynamic Business Process Formation fuses practical needs with theoretical input to present important research innovations in supporting Instant Virtual Enterprises (IVEs). This new organization type brings a combination of business dynamism and explicit business process structure to domains where on-the-fly formation of well-organized business networks is required to deal with the complexity of new products or services under high time pressure. This book contains the main results of the IST CrossWork project, and, importantly, looks beyond the boundaries of this project and sources input from related projects and general trends in collaborative enterprises and the automotive industry. Both the business and technical aspects of Virtual Enterprise coordination are covered within the modular structure of the book, which enables readers from different backgrounds to benefit from the book according to their interests.
Towards New Frontiers: CrossWork -- Business, Organization and Architecture -- Business Aspect -- Organization Aspect -- Architecture Aspect -- CrossWork Technology -- Goal Decomposition and Team Formation -- Business Process Composition -- Business Process Enactment -- The User Perspective -- Domain Knowledge Integration -- Case Studies -- Automotive Industry Case Studies -- Comparable Approaches to IVE -- Conclusion -- Conclusion -- Outlook.
Keywords: Computer science; Artificial intelligence; Information systems; Computer Science; Information Systems Applications (incl. Internet).; Computer Appl. in Administrative Data Processing; Artificial Intelligence (incl. Robotics).